The Effect of Bridge Orientation in Casting Machine on the Castability and Quality of Base Metal Castings - Azamsadat Madani; Ahmad Ghahremanlu; Mohammad Reza Sabooni; Foad Shahabian; Hamzeh Harati (Journal of Dental Materials and Techniques, 2013)
Introduction: The aim of this study was to evaluate the effect of bridge orientation in casting machine on castability and quality of base metal castings. Methods: Three groups of patterns with different direction and lengths in casting machine were casted and then studied qualitatively and quantitatively using mean and standard deviation in table of frequency. Results: Larger nodules and porosities were on the joints of sprue in horizontal specimens (P=0.01 and 0.048, respectively). There was no significant difference in castability between 3-, 5- and 6-unit bridges in relation to their direction in casting machine (P=0.5). An increase in bridge length led to more variation in length and width. The position of bridges also played an important role in the length variation in bridges. Conclusion: The direction of bridges had no effect on base metal castability but a vertical position resulted in a better casting quality and an increase in length of the bridges caused more defects in castings.